2018
DOI: 10.1161/hypertensionaha.117.09767
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 (Transient Receptor Potential Vanilloid 4) Mediates Endothelium-Dependent Contractions in the Aortas of Hypertensive Mice

Abstract: The role of TRPV4 (transient receptor potential vanilloid 4) in regulating vascular contraction in hypertensive mice is poorly established. We tested the hypothesis that TRPV4 regulates endothelium-dependent contractions in aortas from hypertensive mice through the activation of cytosolic cPLA (phospholipase A) and COX2 (cyclooxygenase 2) and identified the possible endothelium-derived contracting factor generated by COX2. Using myography, we demonstrated that GSK1016790A (a TRPV4 agonist) and acetylcholine (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 42 publications
5
54
0
Order By: Relevance
“…It is reported that endothelial cPLA 2 contributes to L‐NAME‐induced hypertension . In line with this notion, we have shown that TRPV4‐mediated cPLA 2 activation contributes to endothelium‐dependent contraction in hypertensive mice . However, the underlying mechanism by which TRPV4 regulates cPLA 2 activity in hypertension has not been defined.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…It is reported that endothelial cPLA 2 contributes to L‐NAME‐induced hypertension . In line with this notion, we have shown that TRPV4‐mediated cPLA 2 activation contributes to endothelium‐dependent contraction in hypertensive mice . However, the underlying mechanism by which TRPV4 regulates cPLA 2 activity in hypertension has not been defined.…”
Section: Discussionsupporting
confidence: 77%
“…We next determined the role of PKCα and ERK1/2 in TRPV4‐mediated cPLA 2 activity. In the previous study, we have demonstrated that stimulation of TRPV4 increases the phosphorylation of cPLA 2 and PLA 2 activity in hypertensive mice . In the present study, we found that inhibition of PKCα and ERK1/2 decreased the TRPV4‐induced phosphorylation of cPLA 2 and PLA 2 activity.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations